Simulation modelling in the sizing of city logistics systems – a study for concentrated delivery points - Bóna, Krisztina; Sárdi, Dávid (International Journal of Engineering and Management Sciences, 2019)
Nowadays, urban freight traffic is causing significant noise and air pollution, so it is in the focus of green logistics developments, both in technology and system organization. Based on experiences within city logistics, significant problems are caused by the so-called concentrated sets of delivery points, where there are several delivery points with heavy freight traffic in a relatively small area. Since the summer of 2015, we collected lots of data about stores of these delivery points to support the modelling and the simulation of the new green solutions for the examined city logistics systems. Based on our results we can say, there are significant savings in these systems, so it is worth to deal with developing new, gateway-concept-based and consolidation-based solutions.